Kaytuesso flavolateralis gen. and sp. nov., a new monotypic genus of Oncomerinae (Hemiptera: Heteroptera: Tessaratomidae) from Papua New Guinea - Carvajal, Mariom A.; Faúndez, Eduardo I.; Rider, David A. (Zootaxa, 2018)
Kaytuesso flavolateralis gen. and sp. nov. is described from Papua New Guinea. The new genus is remarkable in that the only included species is one of the smallest species known within the Oncomerinae. The relationships among Kaytuesso and the related genera Agapophyta Guerin, Erga Walker and Musgraveia Leston and Scudder are discussed.